Pengaruh Waktu Proses Produksi Digital Printing Terhadap Kepuasan Konsumen Pengguna Produk Cetak - Saharja, Komda; Gobal, Raju (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Digital printing products are in great demand by print users, this is because the printing process with digital techniques is in line with consumer expectations. Digital printing products include large / wide format in the form of banners, x-baners, indoor and outdoor promotional media, id cards, pins, brochures, and many more print products that can be made with digital printing processes. Consumers as users of digital printing products have reasons why choosing digital printing techniques in the printing process. The effectiveness factor of the digital printing production process has conformity to consumer choices, so that it affects consumers choosing digital printing as a print technique for processing their orders. Then it can be seen that the time of the production process becomes a separate issue in assessing whether the choice of consumers is not based on the time of the production process. The purpose of this study was to determine the effect of digital printing production process time on consumer satisfaction of print product users. The method used in this study is the ex-postfacto method, the writer examines something that has happened in the field or can be said to research after the incident. The final result of the study states that the production process time does not affect consumers to choose or use digital printing techniques as an option in producing their orders.